Advanced business - Lewis, Roger; Trevitt, Roger ([S.l.] : Nelson Thornes, 1995)
Clearly presents the information covered in the eight mandatory units of the Advanced Business GNVQ.Helps prepare students for the external tests and gives opportunities to practice Key Skills by providing numerous and varied activities.Includes numerous case studies of real businesses.Gives advice on how to go about building a portfolio of evidence.
Keywords: business